Mendelian randomization study reveals the effect of idiopathic pulmonary fibrosis on the risk of erectile dysfunction - Zhang, Kun; Zhou, Jiejun; Li, Anqi; Chen, Mingwei (Frontiers in Medicine, 2023)
Background Several studies have found that erectile dysfunction (ED) is associated with interstitial lung disease. However, the causal relationship between idiopathic pulmonary fibrosis (IPF) and ED risk remains unclear. The present two-sample Mendelian randomization (MR) study aimed to reveal the causal effect of IPF on ED risk. Methods This study included two GWAS summary statistics of IPF (1,028 cases and 196,986 controls) and ED (6,175 cases and 217,630 controls) of European ancestry. The inverse-variance weighted (IVW) was applied as the primary method, and MR-Egger, weighted median, weighted mode, and simple mode were applied as complementary methods to estimate the causal impact of IPF on ED risk. The MR-PRESSO global test and MR-Egger regression were applied to evaluate the pleiotropy. The Cochran’s Q test was applied to examine heterogeneity. The leave-one-out analysis ensured the robustness and reliability of the results. Results Twenty-one genetic variants were obtained as IPF instrumental variables without pleiotropy and heterogeneity. MR analysis using the IVW showed a potential causal relationship between IPF and increased ED risk (ORIVW = 1.046, 95% CI: 1.020–1.073, p = 0.001), and consistent results were obtained with MR-Egger, weighted median, and weighted mode. The leave-one-out analysis showed that no instrumental variables unduly influenced the results. Conclusion This study suggested that IPF may increase the ED risk of the European population.